‘Glues’-the basics and practical applicability in oto-rhino-laryngology and head neck surgery: a review - Munjal, Manish; Munjal, Shubham; Sharma, Saloni; Arora, Vineeta; Kaur, Hardeep; Chawla, Deeksha; Sandhu, Loveleen; Gupta, Dhruv; Gill, Ruchika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Glues or tissue adhesives have attained a foothold in the arena of otorhinolaryngology.and skull base-head neck surgery. At the sites inaccessible to time tested suture application, they facilitate tissue synthesis and local haemostasis, excellent adhesion, elastic consistency, tissue compatibility, and ability to disintegrate and thereby get completely absorbed with time are the properties of an ideal glue tympanoplasty, ossiculoplasty. CSF leak repair are the widely used applications of this suture less modality. Biological and synthetic glues have been developed. The former being the fibrin glues (1940) and the latter, the cyanoacrylates (1960). Moreover in addition to adequate wound closure, a secure fixation of skin grafts, transplants and implants is vital for the success of a surgical intervention. At these crucial sites, tissue adhesives are the preferred option.